RANCANGAN ACAK KELOMPOK TAK LENGKAP SEIMBANG PARSIAL (RAKTLSP) - Gustriza Erda; Tatik Widiharih; Yuciana Wilandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Partially Balanced Incomplete Block Designs (PBIBD) is a design with v treatments arranged into b blocks with every block which is consist of into k treatment (k < v) that in every treatment only occurs once in every block, and there are pair treatment which occur together in the same block as much as λm times. The pair treatments on PBIBD is based on the association scheme. This undegraduate thesis uses triangular association scheme that is two-class association scheme (first and second association). This scheme is used to determine the first and second association of every treatment. Based on formed association, it will obtain the number of pairs treatment that occurs in every block that will be designed (λm, m=1,2). The test that is used is test of treatments effect because only treatments that is important which are adjusted treatment for the reason that not all treatments occurs in every block. Assumptions which is required is the assumption of residual normality, equal variances, and independence assumption. The advanced test to be held is Tuckey Test (Honest Significance Difference). To clarify the discussion on PBID, examples of applications in the field of animal husbandry are given to observe the effect of the type of foods that contain alfalfa effect toward weight gain of turkey. The result obtained indicate that there are significant types of foods that contain alfalfa effect toward weight gain of turkey. Where is the recommended type of food is the food of A that contain 2,5% alfafa type 22.Keywords : PBIBD, Triangular association, Tuckey Test, Normality, Equal Variances, Independence